Tofacitinib in treatment-refractory moderate to severe ulcerative colitis: real-world experience from a retrospective multicenter observational study - Hoffmann, Peter; Globig, Anna-Maria; Thomann, Anne K.; Grigorian, Maximilian; Krisam, Johannes; Hasselblatt, Peter; Reindl, Wolfgang; Gauss, Annika (Journal of Clinical Medicine, 2020)
(1) Background: Tofacitinib is approved in Europe for the treatment of adults with moderately to severely active ulcerative colitis since 2018. Real-world efficacy and safety data are currently scarce. (2) Methods: We performed a retrospective multicenter study at three German tertiary outpatient clinics for inflammatory bowel diseases and included all patients who started tofacitinib therapy between August 2018 and March 2020. The primary endpoint was a combined endpoint of steroid-free clinical remission, steroid-free clinical response, or clinical response at week 8. Secondary endpoints were biochemical response at week 8, as well as steroid-free clinical remission, steroid-free clinical response or clinical response at week 24, respectively, adverse events by week 24, and need for colectomy by the end of follow-up. (3) Results: Thirty-eight patients with moderate-to-severe ulcerative colitis were included. Eleven patients (28.9%) achieved steroid-free clinical remission at week 8. Fifty-three percent of the patients were primary non-responders at week 8. Three severe adverse events (pneumonia, hospitalization for aggravation of ulcerative colitis, emergency colectomy due to colon perforation), and 12 adverse events were documented by week 8 of therapy. By the end of follow-up, seven patients (18.4%) had undergone colectomy.
Gesehen am 22.09.2020